Desain Sumur Resapan Pengolahan Limbah Cucian Mobil X - Mela Ardeline; Revi Lasmita; Winda Yuliana Sari (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
Car washes have become increasingly popular in some areas, but this growth has also had a negative impact on environmental quality, as untreated wash water is often discharged directly into car wash drainage systems without any prior treatment. This discharge of unfiltered wastewater can lead to high levels of COD (chemical oxygen demand) and surfactants in nearby water sources if carried out intensively. Much of the wastewater is often classified as waste. It is discharged by car wash operators into the drainage system and eventually into smaller waterways. In 2014, the Minister of the Environment highlighted the importance of managing cleaning waste due to its harmful effects on the environment and health. Based on the Pekanbaru Municipality's Regional Regulation No. 8 of 2003 on the payment of liquid waste treatment control permit, which stipulates that every industry must carry out waste treatment before discharging into the environment and each industry must also pay a fee, this study will allow the design of absorption wells, which will be used to treat liquid waste from car washes, so that the wastewater absorbed into the ground is no longer a contaminated liquid waste. By treating the waste by the method of infiltration pits, it is hoped that the environment and the health of the residents around the laundry will be well preserved.